Pengaruh Mo dan Ni terhadap Struktur Mikro dan Kekerasan Baja Tahan Karat Martensitik 13Cr [The Effect of Mo And Ni on The Microstructure and Mechanical Properties of 13Cr Martensitic Stainless Steels] - Mabruri, Efendi (Jurnal Metalurgi, 2015)
The 13Cr martensitic stainless steels have been widely used for turbine blade materials in steam turbine system due to high strength, high toughness and good corrosion resistance.This paper reports the effect of Mo and Ni on the microstructure and hardness of 13 Cr martenstitic stainless steel in tempered condition at 625 °C. Optical microscope and SEM-EDS were used for microstructural observation and Rockwell C for hardness testing. The addition of Mo into 13Cr martensitic stainless steel increased delta ferrite content in the microstructure and decreased Rockwell C hardness. On the other hand, the addition of Ni into the steel containing 3%Mo decreased delta ferrite content and increased the hardness. With respect to metal carbide, EDS analysis confirmed the formation of M23C6 in the steels and Mo addition decreased Cr content in the carbide due to partial substitution of Cr with Mo.